2021
DOI: 10.1039/d1fo02539b
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricemic, hepatoprotective and nephroprotective roles of oligopeptides derived from Auxis thazard protein in hyperuricemic mice

Abstract: The oligopeptides derived from Auxis thazard protein (ATO) are a class of small peptides with molecular weight <1 kDa and good bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Specifically, THLPK was shown to have the worst effects on decreasing MDA content, while the effect of LPK was the best ( P < 0.05). Similarly, the oligopeptides derived from Auxis thazard were proved to lower MDA content in the liver . Moreover, the inhibited activity of LDH causes cells to produce ATP through oxidative phosphorylation, which upregulates ROS levels in mitochondria .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, THLPK was shown to have the worst effects on decreasing MDA content, while the effect of LPK was the best ( P < 0.05). Similarly, the oligopeptides derived from Auxis thazard were proved to lower MDA content in the liver . Moreover, the inhibited activity of LDH causes cells to produce ATP through oxidative phosphorylation, which upregulates ROS levels in mitochondria .…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, the oligopeptides derived from Auxis thazard were proved to lower MDA content in the liver. 65 Moreover, the inhibited activity of LDH causes cells to produce ATP through oxidative phosphorylation, which upregulates ROS levels in mitochondria. 66 Compared with the IR-model group, the activity of LDH was significantly inhibited by the oligopeptides (P < 0.05).…”
Section: Oligopeptides Restore the Abnormal Expression And Translocat...mentioning
confidence: 99%
“…As shown in Figure A, molecular weight <1, 1–2, 2–3, and 3–5 kDa in TAP accounted for 91.40, 7.03, 1.11, and 0.46%, respectively, suggesting that TAP may have potential activity. Small molecular weight (1 kDa) oligopeptides tend to exhibit bioactivity and are more easily absorbed by the body . At present, the molecular weight of most identified XOD inhibitory peptides and/or antihyperuricemic peptides is below 1000 Da, such as Ala-Glu-Ala-Gln-Met-Trp-Arg, Ala-Leu-Pro-Met, Leu-Trp-Met, Pro-Glu-Trp, Ala-Leu-Ser-Gly-Ser-Trp, Gly-Gly-Tyr-Gly-Ile-Phe, Met-Ala-Ile-Gly-Leu-Trp, Ala-Cys-Glu-Cys-Asp .…”
Section: Resultsmentioning
confidence: 99%
“…Hyperuricemia is characterized by high levels of UA in serum [ 37 ], and previous studies have shown that some small molecular weight peptides (<1 kDa) could lower the serum UA level [ 18 , 38 , 39 ]. In this study, SISH was confirmed to contain a large number of small peptides (up to 90.7%, <1 kDa) and shown to reduce serum UA levels in hyperuricemic rats, effects that were validated in serum metabolome analysis, as well.…”
Section: Discussionmentioning
confidence: 99%